Compound Schisandra-Ginseng-Notoginseng-Lycium Extract Ameliorates Scopolamine-Induced Learning and Memory Disorders in Mice. (26th July 2017) - Li, Ning; Liu, Cong; Jing, Shu; Wang, Mengyang; Wang, Han; Sun, Jinghui; Wang, Chunmei; Chen, Jianguang; Li, He
Abstract : Schisandra, Ginseng, Notoginseng, and Lycium barbarum are traditional Chinese medicinal plants sharing cognitive-enhancing properties. To design a functional food to improve memory, we prepared a compound Schisandra-Ginseng-Notoginseng-Lycium (CSGNL) extract and investigated its effect on scopolamine-induced learning and memory loss in mice. To optimize the dose ratios of the four herbal extracts in CSGNL, orthogonal experiments were performed. Mice were administered CSGNL by gavage once a day for 30 days and then mouse learning and memory were evaluated by Morris water maze and step-through tests. The mechanisms of CSGNL improving learning and memory were investigated by assaying acetylcholine (ACh) levels and choline acetyltransferase (ChAT) and acetylcholinesterase (AChE) activities in the brain tissues of treated mice. The results showed that CSGNL significantly ameliorated scopolamine-induced learning and memory impairment, at least in part, by modulating ACh levels and ChAT and AChE activities in the mouse brain. Our data support the use of CSGNL as a functional food for learning and memory enhancement.